Simple Approach to Bandwidth Enhancement Of Compact Pifa For Wireless System Applications - Ikechiamaka, Florence Nwamaka; A, Akinbolati; C, Okpala (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
Bandwidth is a critical parameter that must be considered in the design of electrically small antennas for compact wireless system. In order to overcome the demerit of narrow bandwidth, a simple method of bandwidth enhancement through parametric study of PIFA is proposed. The PIFA understudied was designed and simulated by the use of theoretical equations based on transmission line model and High Frequency Structural Simulator (HFSS) respectively. It has initial bandwidth of  The study reveals that by reducing the size ratio of the planar element (radiating patch) of PIFA, bandwidth enhancement of  was achieved. Increasing the distance between short plate and feed gave rise to  increment in bandwidth while increasing the length of ground plane while keeping the width of ground plane constant enhanced bandwidth by .  The designed compact PIFA of patch size  can be employed in wireless systems such as cell phone  and implantable medical devices .